2015
DOI: 10.1039/c5fo00602c
|View full text |Cite
|
Sign up to set email alerts
|

Sea cucumber cerebrosides and long-chain bases from Acaudina molpadioides protect against high fat diet-induced metabolic disorders in mice

Abstract: Metabolic syndrome (MS) is a cluster of metabolic disorders such as abdominal obesity, hypertension, glucose intolerance, dyslipidemia and hepatic steatosis that contribute to increased cardiovascular morbidity and mortality. There is an urgent need for strategies to prevent this emerging global epidemic. Recently, growing interest in discovering food functional nutrients for the prevention and treatment of MS has generated. In the present study, sea cucumber cerebrosides (SCC) and the main structural units, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
2
22
1
Order By: Relevance
“…Hyperlipidemia, characterized by elevated levels of TGs in plasma or serum is one of the metabolic disorders induced by feeding a high-fat diet to C57BL/6J mice [4648]. In our study, XN significantly decreased plasma TG levels in diet-induced obese C57BL/6J mice.…”
Section: Discussionsupporting
confidence: 53%
“…Hyperlipidemia, characterized by elevated levels of TGs in plasma or serum is one of the metabolic disorders induced by feeding a high-fat diet to C57BL/6J mice [4648]. In our study, XN significantly decreased plasma TG levels in diet-induced obese C57BL/6J mice.…”
Section: Discussionsupporting
confidence: 53%
“…Sphingolipids of marine invertebrates have a unique triene type of sphingoid bases with a conjugated diene such as 2-amino-4,8,10-octatriene-1,3-diol (d18:3) and 2-amino-9-methyl-4,8,10-octatriene-1,3-diol (d19:3). The first studies devoted to investigating holothurian sphingolipids indicated that three types of major LCBs of the sea cucumber cerebrosides (d17:1, d18:2, and t17:1) isolated from Apostichopus japonicus , Cucumaria frondosa and Acaudina molpadioides [ 94 , 95 ]. Sugawara et al [ 96 ] found d17:1, d18:1, d18:2, d18:3, d19:1, d19:2 and d19:3 in the sea cucumber S. horrens .…”
Section: Biologically Active Compounds With Anticancer Activitymentioning
confidence: 99%
“…Diets containing 1.0% SDG significantly reduced visceral fat accumulation by 32.3%, liver fat accumulation by 25.6%, hyperlipaemia by 37.9%, and hypercholesterolaemia by 14.9% . Sphingolipids may possibly contribute to the beneficial effect of WG wheat intake in the prevention of diabetic development . Antidiabetic effects of simple phenolic acids, such as gallic acid, syringic acid, ferulic acid, caffeic acid, p‐coumaric acid, sinapic acid, and cinnamic acid, in rodents have been recently reviewed .…”
Section: Health‐promoting Effects Of Wheat Phytochemicalsmentioning
confidence: 99%